2020
DOI: 10.1371/journal.pone.0236001
|View full text |Cite
|
Sign up to set email alerts
|

Germination response of diverse wild and landrace chile peppers (Capsicum spp.) under drought stress simulated with polyethylene glycol

Abstract: Responses to drought within a single species may vary based on plant developmental stage, drought severity, and the avoidance or tolerance mechanisms employed. Early drought stress can restrict emergence and seedling growth. Thus, in areas where water availability is limited, rapid germination leading to early plant establishment may be beneficial. Alternatively, germination without sufficient water to support the seedling may lead to early senescence, so reduced germination under low moisture conditions may b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Perlakuan stress kekeringan dengan pemberian PEG 20% pada padi Lokal Lampung tidak memberikan pengaruh terhadap perkecambahan (Chrisnawati et al, 2020). Namun pemberian konsentrasi PEG 20% pada plasmanutfah cabai lokal Meksiko menyebabkan terhambatnya perkecambahan benih cabai (Bernau et al, 2020). (Millah et al, 2021)melakukan skiring 22 genotipe cabai koleksi IPB menggunakan konsentrasi PEG 15%.…”
Section: Pendahuluanunclassified
“…Perlakuan stress kekeringan dengan pemberian PEG 20% pada padi Lokal Lampung tidak memberikan pengaruh terhadap perkecambahan (Chrisnawati et al, 2020). Namun pemberian konsentrasi PEG 20% pada plasmanutfah cabai lokal Meksiko menyebabkan terhambatnya perkecambahan benih cabai (Bernau et al, 2020). (Millah et al, 2021)melakukan skiring 22 genotipe cabai koleksi IPB menggunakan konsentrasi PEG 15%.…”
Section: Pendahuluanunclassified
“…Drought stresses simulated by PEG at 20% were reported to delay germination in all tested pepper (Capsicum spp.) genotypes (Bernau et al 2020). Drought stress simulated by PEG 6000 at germination stages significantly changed soluble protein content, peroxidase activity, and malondialdehyde in Larix olgensis A. Henry.…”
Section: Introductionmentioning
confidence: 97%
“…In wild and landrace chile pepper, local adaptation may also be possible, where individuals (referred to as accessions) originating from low precipitation environments may possess elevated tolerance to soil water deficit. For example, a recent germination study identified adaptive responses in chile pepper associated with precipitation [ 15 ]. Landraces from hotter, drier ecozones had significantly delayed germination, suggesting a possible adaptive response related to drought avoidance.…”
Section: Introductionmentioning
confidence: 99%